PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. MEDISAFE TECHNOLOGIES - Sitorus, Ayu Rona; Sinulingga, Nurbeti (Universitas Quality, 2023)
Based on the result of the research it is obtained partialeously that the work produktivity of employees on Office PT. Medisafe Technologies Medan is influenced by work Healt and Safety, this is proved by partial (uji t) with value t hitung 11.598 t tabel 1,661 with significant (Sig)0,0000,05.The result of the analysis proved that the coefficient value of determination R Square is 0,594%. Therefore, it is know that work productivity variation influenced by work health and safety variable is 59,4%, while 46,6% is influenced by other variables that are not discussed in this studied such as training, mental and physical abilities, relationship between superiors and subordinates and others variables.